Оформлення повноважень адвоката в цивільному процесі - Єфіменко, М. Ю.; Yefimenko , M. Yu. (Вісник Маріупольського державного університету. Серія : Право. - 2014. - Вип. 7. - С. 181-188, 2014)
У статті розглянуто актуальні проблеми в сфері оформлення повноважень адвоката в цивільному процесі. Проаналізовано правовий статус адвоката, його функції та завдання на підставі діючих нормативних актів. Встановлено процедуру видачі документів на представництва адвоката. Зроблено висновок про те, що основною функцією адвоката в цивільному процесі є представницька, у межах якої додатково реалізуються консультативна, превентивна, відновлювальна та охоронна функції. Адвокат в цивільному процесі виступає особливим суб’єктом процесуальних правовідносин, допущеним до участі судом з кола визначених законом осіб з метою захисту і забезпечення належної реалізації прав і обов’язків осіб, зацікавлених у результатах розгляду справи. Пропонується визначення значення інституту судового представництва як процесуальної форми участі адвоката в цивільному процесі на підставі договору або доручення.

The success of democratic transformations in Ukraine is impossible without effective legal regulation of activities of the subjects, authorized to provide legal aid. One of these subjects is a lawyer, to whose principal tasks belong Ukrainian citizens’, foreign citizens’, juridicial persons’, individuals’ without citizenship protection of rights assistance, representation of their legitimate interests and other legal aid rendering. The tasks enumerated are also performed by a lawyer in the course of civil procedure. Although, the activities of lawyers as participants of civil procedure contain a range of disadvantages, with adversely affect the level of public confidence. In particular, the overwhelming majority of lawyers perform the role of an observer in a judicial proceeding, what influences negatively the quality of rendering legal aid to citizens and juridicial persons as well as their legitimate interests representation and other legal aid provision. Lawyers’activity, being a variety of social-legal activity, is performed mainly in private interests, having generally public character. Public legal tasks oblige lawyers to provide free legal service in cases determined by legislation. Traditionally, lawyers participate in civil procedure in accordance with contractual processual representation or voluntary representation. Contractual representation is a variety of representation, the reason of appearance of which is a representative’s and a mandator’s will. In other words, it is based on a contract. In a civil procedure, a lawyer is a subject of a voluntary processual representation. An obligatory condition for such position in a civil procedure acquiring is processual juridicial personality possession. Since the moment of acquiring the status of a voluntary representative in the law proceeding, the subject mentioned possesses not only general rights and responsibilities, determined by the legislation for the sphere of lawyer activities, but also special processual rights and duties. The legalization of the powers in course of civil procedure is performed under the authority of a power of attorney. A contract about legal aid providing is a variety of a power of attorney. The asset 1007 of The Civil Codex of Ukraine presupposes the duty of a mandator to give to a representative a power of attorney to accomplish juridicial actions, enumerated in a letter of attorney. Thus, a client should confer, when necessary, a power of attorney, and it is under its authority (but not under the authority of a warrant), that lawyers, who work individually or as a member of a board, should act.

В статье рассмотрены актуальные проблемы в сфере оформления полномочий адвоката в гражданском процессе. Проанализирован правовой статус адвоката, его функции и задачи на основании действующих нормативных актов. Установлена процедура выдачи документов на представительства адвоката. Сделан вывод о том, что основной функцией адвоката в гражданском процессе является представительская, в рамках которой дополнительно реализуются консультативная, превентивная, восстановительная и охранная функции. Адвокат в гражданском процессе выступает особым субъектом процессуальных правоотношений, допущенным к участию судом из круга определенных законом лиц с целью защиты и обеспечения надлежащей реализации прав и обязанностей лиц, заинтересованных в результатах рассмотрения дела. Предлагается определение значения института судебного представительства как процессуальной формы участия адвоката в гражданском процессе на основании договора или поручения.
Legalization of lawyer’s powers in civil procedure
Keywords: адвокат; представництво; повноваження; цивільний процес; надання правової допомоги; lawyer; representative office; powers; civil process; provision of legal aid; адвокатская деятельность; представительство; полномочия; гражданский процесс; предоставление правовой помощи